Correlação dos aspectos laparoscópicos com as alterações histológicas glandulares das lesões endometrióticas peritoneais - Viscomi, Francesco Antonio [UNESP]; Dias, Rogério [UNESP]; Luca, Laurival De [UNESP]; Franco, Marcello Fabiano De [UNESP]; Ihlenfeld, Mauro Fernando Kürten [UNESP] (Associação Médica Brasileira, 2004)
OBJECTIVE: To evaluate the correlation between laparoscopic aspects and glandular hystological findings of peritoneal endometriosis to understand the theory of evolution of endometriosis. METHODS: Sixty seven women with peritoneal endometriosis were submitted to laparoscopy. Peritoneal biopsy was taken from the typical (puckered black) and atypical endometriotic implants. The different aspects of endometriosis were classified as follows: red lesions (group V), black lesions (group N) and white lesions (group B). Hystological sections were examined according to a standardized protocol. The hystological parameters used were: functional characteristics of glandular epithelium, presence of intraluminal debris, occurrence of mitosis and stroma/gland ratio. RESULTS: Functional characteristics of glandular epithelium showed statistically significant association among groups. Secretory epithelium was found in 68.4 % of group V, in 15.8% of groups N & B, while not characteristic epithelium was found in 19.4% of red lesions, 38.7% of black lesions and 41.9% of white lesions. Proliferative epithelium was found in 50% of group B patients and in 25% of groups V & N (p=0.011). Regarding intraluminal debris, there were also statistically significant differences among the groups, present in 58.4% of group N, 33.3% of group B and 8.3% of group V (p=0.016). There was no statistical difference between occurrence of mitosis (P=0.428), nor in the stroma/gland ratio (p=0.159). CONCLUSION: Association between functional activity and red lesions and low activity in black and white lesions, regarding the hystological characteristics of the glandular epithelium analyzed in this study shows the importance of the theory of evolution of endometriosis. This was also demonstrated by presence of intraluminal debris in the study groups.

OBJETIVOS: Correlacionar os aspectos laparoscópicos com os achados histológicos na endometriose peritoneal para facilitar a compreensão da teoria evolutiva da endometriose. MÉTODOS: Foram selecionadas aleatoriamente para o presente estudo prospectivo 67 pacientes submetidas a laparoscopia, com diagnóstico de endometriose peritoneal. A avaliação laparoscópica foi baseada no aspecto visual do implante suspeito de endometriose peritoneal, submetido a estudo anatomopatológico. De acordo com o aspecto laparoscópico, as lesões foram agrupadas em: grupo V - vermelhas, grupo N - negras, grupo B - brancas. A avaliação histológica foi realizada observando-se as características funcionais do epitélio glandular, a presença de debris intraluminais, o número de mitoses e a relação estroma/glândula. RESULTADOS: As características funcionais do epitélio glandular mostraram associação estatisticamente significante entre os grupos, sendo o epitélio com carcterística secretora encontrado em 68,4% das lesões do grupo V, 15,8% do grupo N e B, enquanto que o epitélio incaracterístico foi encontrado em 19,4% das lesões vermelhas, 38,7% das lesões negras e 41,9% das brancas e o epitélio proliferativo foi observado em 50% das pacientes do grupo B e em 25% dos grupos V e N (p=0,011). Em relação à presença de debris intraluminais, também houve diferença significante entre os grupos, estando presentes em 58,4% das lesões negras, 33,3% das lesões brancas e 8,3% das lesões vermelhas (p=0,016). Quanto ao número de mitoses, não houve diferença significante nos três grupos de estudo (p=0,428). O mesmo foi observado na relação estroma/glândula, não havendo diferença significante nos grupos de estudo (p=0,159). CONCLUSÃO: A associação entre atividade funcional nas lesões vermelhas e baixa atividade funcional nas lesões negras e brancas, bem como a presença de debris intraluminais nos diferentes grupos, reforçam a teoria evolutiva da endometriose peritoneal.
Correlation between laparoscopic aspects and glandular hystological findings of peritoneal endometriotic lesions
Keywords: Endometriosis; Laparoscopy; Histology; Types of lesions; Endometriose; Laparoscopia; Histologia; Tipos de lesões